2019
DOI: 10.1186/s12885-019-6214-z
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated neuroendocrine rectal carcinoma with uncommon immune-histochemical features and clinical presentation with a subcutaneous metastasis, treated with first line intensive triplet chemotherapy plus bevacizumab FIr-B/FOx regimen: an experience of multidisciplinary management in clinical practice

Abstract: BackgroundNeuroendocrine tumors (NETs) are heterogeneous, widely distributed tumors arising from neuroendocrine cells. Gastrointestinal (GI)-NETs are the most common and NETs of the rectum represent 15, 2% of gastrointestinal malignancies. Poorly differentiated neuroendocrine carcinomas of the GI tract are uncommon. We report a rare case of poorly differentiated locally advanced rectal neuroendocrine carcinoma with nodal and a subcutaneous metastasis, with a cytoplasmic staining positive for Synaptophysin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
6
1
Order By: Relevance
“…Many studies illustrated a poorer prognosis of colorectal compared to pancreatic NEC [21], despite of the similar response to chemotherapy [22,23]. Still, many HGNECs patients were present with advanced-or late-stage disease, approximately 50% of the NEC patients with synchronous metastatic disease [5,24], due to the lack of early symptoms [1], and there is a lack of the optimal treatment HGNECs of the colon and rectum [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies illustrated a poorer prognosis of colorectal compared to pancreatic NEC [21], despite of the similar response to chemotherapy [22,23]. Still, many HGNECs patients were present with advanced-or late-stage disease, approximately 50% of the NEC patients with synchronous metastatic disease [5,24], due to the lack of early symptoms [1], and there is a lack of the optimal treatment HGNECs of the colon and rectum [9].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of CRNEC and the resulting di culty to accumulate a large cohort for evaluation, there are few retrospective studies and almost no prospective studies to evaluate its prognostic value of AC [2], resulting in the fact that, due to the histological and clinical resemblance, treatment is more likely in analogy to the much more common SCLC [1,20], with platinum-based chemotherapy as a cornerstone [9]. In clinical practice, relevant features addressing the optimal management strategy of NECs consists of clinical behavior, mitoses, Ki-67 expression, morphology and so on [5]. Bearing the high relapse rate following radical surgery in mind, platinum-based AC in this setting would be advocated, although it was not supported by su cient evidence, with no randomized studies ever addressing the effect [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, FIr-C/FOx-C induced LTS 65.5%, significantly more represented by LTS-ms (59%) vs. LTS-ss, prevalently LT plus other at least G2 non-limiting toxicities (34%) or ≥2 LTs (24%) ( 5 ). We previously showed that LTS monitoring could enhance evaluation of individual safety profile also in other different cancer settings ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%